Effect of different litter materials on growth performance, the gait score and footpad dermatitis, carcass parameters, meat quality, and microbial load of litter in broiler chickens - Durmus, M.; Kursun, K.; Acik, I. Polat; Tufan, M.; Kutay, H.; Benli, H.; Baylan, M. (Elsevier, 2023)
In the current study, the microbial load of litter materials, growth performance, the gait score and footpad dermatitis, carcass characteristics, and meat quality of broilers reared on different litter materi-als were investigated. After hatching and sex determina-tion, the chicks were allocated to 3 different experimental groups with each having 8 replications. The chicks were reared on thick sawdust, fine sawdust, or rice hull litter materials. A total of 480 chicks were used with each replicate having 20 chicks (10 males, 10 females) of similar body weight. At the end of the experi-ment, a total of 96 chickens were slaughtered, 32 from each group with equal number of males and females. The effect of the experimental groups on body weight, mortality, and carcass characteristics were not significant; however, feed consumption and feed conver-sion ratio were significantly (P < 0.05) affected by the treatments in all weeks except the first 2 wk of the exper-iment. Different litter materials significantly (P < 0.05) influenced the foot health of the chickens as well as the microbial load of the litter. There was no significant dif-ference between the treatment groups in terms of pH, color, and cutting resistance of raw meat however, the water loss during the cooking of the meat and the TPA analysis results such as hardness, springiness, and chewi-ness of the cooked meats were significantly (P < 0.05) affected by the type of litter material. It was concluded that the use of fine sawdust from trees such as pine and larch containing antimicrobial extracts would be more appropriate as a litter material in broiler production.
Keywords: Broiler; Footpad Dermatitis; Litter Material; Meat Quality; Microbial Load; Pad Dermatitis